The goal-directed model as an alternative to reductionist and network approaches of psychopathology. (October 2021) - Moors, Agnes; Boddez, Yannick
Abstract: As an alternative to biological reductionist and network approaches to psychopathology, we propose a nonreductionist mental-mechanistic approach. To illustrate this approach, we work out the implications of the goal-directed framework of Moors et al., which has the potential to explain the heterogeneous manifestations of psychopathology with a restricted set of broad theoretical principles.